High-specific-strength multistage twin-crystal martensite structure titanium alloy and preparation method thereof
Through the Ti-Al-Mo-Nb-V-Cr-Fe component system and hot-rolling current heat treatment process, a titanium alloy with a multi-stage twin martensite structure is formed, which solves the shortcomings in strength and density of titanium alloy materials, and achieves the realization of the need for titanium alloy materials. The combination of high strength and high plasticity reduces process costs and complexity, and is suitable for applications in the fields of oceans and space.
Patent Information
- Application Number
- CN202411077122.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
AI Technical Summary
Existing titanium alloy materials cannot achieve higher comprehensive performance after heat treatment, especially in reducing density and increasing strength. The traditional process is costly and complex, which affects the in-depth application of materials in the fields of oceans and space. Exploring.
Ti-Al-Mo-Nb-V-Cr-Fe is used as the component system, and the power-on time during current heat treatment is controlled through a process combining hot rolling and current heat treatment to form a titanium alloy with a multi-stage twin martensite structure. Regulates its microstructure to increase strength and retain plasticity.
The high specific strength of titanium alloy is achieved, the room temperature tensile yield strength can reach more than 1320MPa and the tensile strength can reach more than 1400MPa. At the same time, it reduces material density and processing difficulty, reduces process costs, reduces carbon emissions, and meets the titanium alloy. Preparation in high performance requirements.
Smart Images

Figure CN119120985A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloys, and in particular to a high specific strength multi-level twin martensitic structure titanium alloy and a preparation method thereof. Background Art
[0002] Titanium alloys are widely used in aviation, chemical, biomedical, marine and other fields due to their excellent comprehensive mechanical properties, such as high strength, good corrosion resistance and good biocompatibility. Among the commercial titanium alloys, TC4 is the most commonly used, and its strength is usually in the range of 900-1000MPa. With the deeper exploration of the ocean and space, the comprehensive performance of titanium alloy materials has been challenged, especially for reducing material density and improving material strength.
[0003] After traditional heat treatment, titanium alloys usually have four typical structures, namely equiaxed structure, basket structure, dual structure and lamellar structure. However, the performance brought by these structures can never reach a higher level. Summary of the invention
[0004] According to one embodiment of the present invention, the purpose is to provide a titanium alloy with a multi-level twin martensitic structure having high specific strength and a preparation method thereof. The titanium alloy in the present invention has high specific strength while being able to retain the plasticity of the material from being too low.
[0005] The above purpose can be achieved by implementing the following technical solutions:
[0006] According to one aspect of the present invention, the present invention provides a high specific strength multi-level twinned martensitic structure titanium alloy, the component system of the titanium alloy is: Ti-Al-Mo-Nb-V-Cr-Fe; the weight percentage of each element is: Al: 6% to 9%; Mo: 0.5% to 2%; Nb: 0.5% to 2%; V: 0.2% to 1.5%; Cr: 0.2% to 1.5%; Fe: 0.2% to 1.5%, and the balance is Ti and inevitable trace impurities.
[0007] Furthermore, the titanium alloy consists of martensite α' phase.
[0008] Furthermore, the titanium alloy is prepared by combining hot rolling and electric current heat treatment, by controlling the power-on time during the electric current heat treatment.
[0009] Furthermore, the titanium alloy has martensite of different scales and a multi-level twin structure inside.
[0010] Furthermore, the martensite is 0.1 to 10 μm long, and has an aspect ratio of 1:1 to 1:20.
[0011] Optionally, in the titanium alloy, Al: 6.5% to 8.5%.
[0012] Optionally, in the titanium alloy, Mo≤1.5%; Nb≤1.5%; V≤1%; Cr≤1%; Fe≤1%.
[0013] Optionally, the titanium alloy has a room temperature tensile yield strength greater than 1200 MPa, a room temperature tensile strength greater than 1300 MPa, and a room temperature elongation greater than 6.0%.
[0014] According to another aspect of the present invention, a method for preparing a high specific strength multi-level twinned martensitic structure titanium alloy is provided by combining hot rolling and electric current heat treatment, and the preparation is performed by controlling the power-on time during the electric current heat treatment, comprising the following steps:
[0015] Step 1), weighing the raw materials of each element according to weight percentage;
[0016] Step 2), placing the raw materials into a vacuum arc melting furnace, evacuating the furnace, filling with argon as a protective gas, and repeatedly melting for multiple times to obtain an ingot;
[0017] Step 3), placing the ingot in a vacuum heating furnace for heat preservation, and then annealing by furnace cooling;
[0018] Step 4), heating and heat-insulating the annealed ingot under an inert gas protection atmosphere, and hot rolling to obtain a titanium alloy plate;
[0019] Step 5), subjecting the titanium alloy plate to current heat treatment and water quenching to obtain a high specific strength multi-level twin martensitic structure titanium alloy.
[0020] Furthermore, the step of subjecting the titanium alloy plate to current heat treatment and water quenching to obtain a high specific strength multi-level twinned martensitic structure titanium alloy refers to using copper electrodes to clamp the titanium alloy plate, applying a power-on voltage, controlling the power-on time, and water quenching to obtain a high specific strength multi-level twinned martensitic structure titanium alloy.
[0021] Optionally, when the power-on voltage is 220V, the power-on heating time is controlled to be 3 to 6s.
[0022] Optionally, in step 3), the insulation temperature is 1000° C. to 1200° C., and the insulation time is 4 h to 7 h.
[0023] Optionally, in step 4), the heating and insulation temperature is 900° C. to 1000° C., and the insulation time is 30 min to 60 min; during hot rolling, the pressing amount for each pass is controlled to be 1 mm to 0.5 mm.
[0024] Optionally, during hot rolling, when the sample thickness is ≥8mm, the pressing amount per pass is 1mm; when the sample thickness is 4mm≤<8mm, the pressing amount per pass is 0.75mm; when the sample thickness is <4mm, the pressing amount per pass is 0.5mm, until the thickness of the ingot reaches the target thickness.
[0025] Beneficial effect: According to one embodiment of the present invention, by optimizing the alloying elements of the titanium alloy, using Ti-Al-Mo-Nb-V-Cr-Fe as the composition system (nominal composition), and optimizing the ratio of each element, the microstructure of the titanium alloy is regulated to form a titanium alloy with a multi-level twinned martensitic structure. The titanium alloy has high specific strength. For example, its room temperature tensile yield strength can reach more than 1320 MPa, and its room temperature tensile strength can reach more than 1400 MPa.
[0026] Compared with the prior art, the embodiments of the present invention also have the following advantages:
[0027] 1) In the present invention, there are fewer β-stabilizing elements in the constituent elements of the titanium alloy. Trace amounts of β-stabilizing elements can produce a good solid solution strengthening effect and effectively improve the strength of the alloy; fewer β-stabilizing elements reduce the density of the material and reduce the difficulty of material processing; and the content of Mo, Nb and V elements is relatively low, making the alloy price even cheaper. The inventors of the present application recognize that although more β-stabilizing elements in titanium alloys, such as Mo, V, Nb and Zr, can effectively improve the strength of the material, excessive addition will increase the density of the material, increase the weight of the material, and increase the difficulty of material processing. In particular, too many types of elements with high specific gravity will make it difficult to ensure the uniformity of the composition during the smelting process. In the present application, there are fewer types of elements with high specific gravity, and iron, chromium, titanium, aluminum, and vanadium, which have a low specific gravity, are selected. Zirconium with a high specific gravity is not included, which further ensures the uniformity of the composition during the smelting process.
[0028] 2) The titanium alloy of the present invention has a multi-level twin martensitic structure, martensite of different scales and the multi-level twin structure inside, with high specific strength and retained plasticity. Since titanium alloy is also divided into high-temperature phase β and low-temperature phase α, combined with the martensitic structure that can improve the strength of steel materials, the present application obtains the martensitic structure through quenching, which further improves the strength of the titanium alloy. Usually, martensite will sacrifice the plasticity of the material to a large extent while improving the strength. However, the titanium alloy of the present application, due to the presence of multi-level twin structures in the martensite and inside, can not only improve the strength of the material, but also the twin boundary can retain plasticity. Therefore, the material strength is improved without sacrificing the plasticity of the material to a large extent.
[0029] 3) Based on a specific titanium alloy ratio, this application adopts hot rolling and electric current heat treatment process to more effectively control the microstructure of titanium alloy. By using electric current heat treatment after hot rolling, the cost of heat treatment and titanium alloy preparation is greatly reduced, the process complexity is reduced, and carbon emissions are reduced.
[0030] 4) The present invention adopts hot rolling and electric current heat treatment processes under the titanium alloy formula. By controlling the power-on time during the electric current heat treatment, the mechanical properties of the titanium alloy can be controlled, thereby meeting the preparation requirements of titanium alloys with various properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 1 is a microstructure diagram of a high specific strength multi-level twinned martensitic structure titanium alloy obtained in Example 1 of the present invention;
[0032] Figure 2 This is a morphology diagram of the multi-level twinned martensite in the high specific strength multi-level twinned martensitic structure titanium alloy obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In one embodiment of the present application, a high specific strength multi-level twin martensitic structure titanium alloy is provided, in which the weight percentage of each element is: Al: 6% to 9%; Mo: 0.5% to 2%; Nb: 0.5% to 2%; V: 0.2% to 1.5%; Cr: 0.2% to 1.5%; Fe: 0.2% to 1.5%, and the balance is Ti and inevitable trace impurities. By optimizing the alloying elements of the titanium alloy, using Ti-Al-Mo-Nb-V-Cr-Fe as the component system, optimizing the ratio of each element, and regulating the microstructure of the titanium alloy, a titanium alloy with a multi-level twin martensitic structure is formed, and the titanium alloy has a high specific strength.
[0035] When the Al content is controlled to be not less than 6% in the present invention, solid solution strengthening can be formed to improve the material strength. In a preferred embodiment, in the titanium alloy, the weight percentage of the element Al is: Al: 6.5% to 8.5%. By further controlling the Al content to be not less than 6.5%, for example, 6.5%, 7.0%, 7.2%, 7.4%, 7.6%, 8.0%, 8.5%, etc., it is more conducive to forming solid solution strengthening and greatly improving the material strength; and controlling the Al content to be not more than 9% can prevent the generation of Ti-Al compounds and affect the plasticity of the material.
[0036] In addition, in the present invention, unavoidable impurities refer to C, H, O, N, etc., and the content of the total unavoidable impurities is ≤2.5%. Among them, C≤0.05%; H≤0.01%; O≤0.1%; N≤0.04%, and the content of other elements is ≤0.01%; and the above percentages are all weight percentages.
[0037] In the present invention, the amount of β-stabilizing elements is strictly controlled, especially the upper limit of each element. In a preferred embodiment, the upper limit of β-stabilizing elements in the titanium alloy is further controlled to be: Mo≤1.5%; Nb≤1.5%; V≤1%; Cr≤1%; and Fe≤1%. This preferred embodiment can achieve better results by further controlling the upper limit of more β-stabilizing elements in the titanium alloy. A smaller amount of β-stabilizing elements can effectively improve the strength of the alloy while significantly reducing the density of the material and reducing the alloy cost.
[0038] A method for preparing a high specific strength multi-level twinned martensitic structure titanium alloy provided in one embodiment of the present application is to prepare the titanium alloy by combining hot rolling and electric current heat treatment, and controlling the power-on time during the electric current heat treatment to achieve control of the mechanical properties of the titanium alloy, thereby meeting the preparation requirements of the titanium alloy. More specifically, the following steps may be included.
[0039] Step 1) weighing the raw materials of each element according to weight percentage. Each element may be a high-purity single substance with a purity greater than or equal to 99%. Further, weighing high-purity titanium, high-purity aluminum, high-purity molybdenum, high-purity niobium, high-purity vanadium, high-purity chromium, and high-purity iron with a purity of ≥99.99%.
[0040] Step 2), placing the raw materials in a vacuum arc melting furnace, evacuating the furnace, filling with argon as a protective gas, and repeatedly melting for multiple times, for example, 3 to 7 times, to obtain an ingot.
[0041] Step 3), vacuum annealing the ingot: first, place the ingot in a vacuum heating furnace for insulation at a temperature of 1000°C to 1200°C for 4h to 7h, and then anneal it in a furnace cooling manner.
[0042] Step 4), heating and keeping the annealed ingot in an inert gas protective atmosphere, the heating and keeping temperature is 900°C to 1000°C, and the keeping time is 30min to 60min; hot rolling is performed with the pressing amount of each pass controlled to be 1mm to 0.5mm to obtain a titanium alloy plate.
[0043] Through hot rolling, a large number of dislocations are generated inside the material, including edge dislocations, screw dislocations and compound dislocations, among which screw dislocations are conducive to the generation of a large number of twins in subsequent heat treatment. In addition, during hot rolling, by controlling the amount of pressure per pass within the range, it is possible to prevent the material from being crushed due to excessive pressure in a single pass. Further preferably, during hot rolling, when the sample thickness is ≥8mm, the amount of pressure per pass is 1mm; when 4mm≤sample thickness<8mm, the amount of pressure per pass is 0.75mm; when the sample thickness is <4mm, the amount of pressure per pass is 0.5mm, until the thickness of the ingot reaches the target thickness, which may be, for example, 2mm.
[0044] Step 5), the titanium alloy sheet is subjected to current heat treatment and water quenching to obtain a high specific strength multi-level twin martensitic titanium alloy. The current heat treatment refers to clamping the titanium alloy sheet with copper electrodes, applying voltage to it and controlling the heating time, and then water quenching to obtain a high specific strength multi-level twin martensitic titanium alloy. It should be noted that the current heat treatment method of the present invention can also be applied to other metal materials, not limited to the titanium alloy sheet of the present application.
[0045] In addition, the inventors also realized that: under the same conditions, within a certain range, increasing the power-on time will increase the room temperature tensile yield strength, tensile strength and elongation of the material; while excessively increasing the power-on time will lead to a decrease in material strength and plasticity. Preferably, under the titanium alloy component system formula of the present invention, hot rolling and current heat treatment processes are used for preparation, and when the power-on voltage is 220V, the power-on heating time can be controlled to 3 to 6 seconds to obtain a titanium alloy with excellent room temperature tensile yield strength, room temperature tensile strength and room temperature elongation.
[0046] Through observation and detection, it was found that the titanium alloy obtained by the present invention is composed of martensite α' phase. The titanium alloy has a multi-level twin structure in martensite of different scales and inside. The martensite is 0.1 to 10 μm long and has an aspect ratio of 1: (1-20). That is, the martensite of different scales and the multi-level twin structure inside constitute the titanium alloy with high specific strength multi-level twin martensite structure of the present invention.
[0047] In addition, the titanium alloy obtained by the present invention has high specific strength and excellent mechanical properties. As shown in Examples 1 to 6, the room temperature tensile yield strength of the titanium alloy is greater than 1200 MPa, the room temperature tensile strength is greater than 1300 MPa, and the room temperature elongation is greater than 6.0%.
[0048] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can be obtained from commercial channels unless otherwise specified. The methods described are conventional methods unless otherwise specified.
[0049] The specific test methods of the following embodiments are as follows: the microstructure of the sample is observed by transmission electron microscopy; the yield strength, tensile strength and fracture strain of the sample are tested for tensile properties according to international standards (Chinese GB / T 228-2002).
[0050] Embodiment 1:
[0051] The nominal composition of the titanium alloy in this embodiment is Ti-7Al-Mo-Nb-V-Cr-Fe, which is Al: 7%; Mo: 1%; Nb: 1%; V: 0.5%; Cr: 0.5%; Fe: 0.5%, and the remainder is Ti and unavoidable impurities.
[0052] Preparation: 1) Put the raw materials of high-purity titanium, high-purity aluminum, high-purity molybdenum, high-purity niobium, high-purity vanadium, high-purity chromium and high-purity iron (purity ≥ 99.99%) into a vacuum arc melting furnace, evacuate and pass argon protection, repeatedly melt the ingot 5 times to obtain a uniform button ingot. 2) Put the button ingot into a vacuum heating furnace, keep it at 1100℃ for 6h, and then anneal it by furnace cooling. 3) Put the annealed ingot into a vacuum atmosphere furnace at 980℃, pass argon atmosphere to protect the ingot from oxidation, and keep it warm for 45min. 4) Take out the heated ingot and immediately put it into the hot rolling mill roll for rolling. When the thickness is greater than or equal to 8mm, the single pass pressure is 1mm; when the thickness is greater than or equal to 4mm, the single pass pressure is 0.75mm; finally, a single pass pressure of 0.5mm is used to roll the ingot to a final thickness of 2mm.
[0053] 5) The burrs around the rolled plate are cut off and the surface is polished. Then, it is clamped in a copper electrode and a 220V voltage is applied for 3 seconds. Then, the electrode is immediately released to drop the plate into water and quench it to obtain a titanium alloy with a high specific strength multi-level twin martensitic structure.
[0054] The titanium alloy with high specific strength and multi-level twin martensitic structure prepared in this embodiment has a microstructure diagram as shown in FIG. Figure 1The titanium alloy of this embodiment has a matrix composed of martensite and twins (i.e., composed of titanium alloy martensite α' phase), wherein the martensite is 0.1-2 μm long and has an aspect ratio of 1:1-1:12; and primary and secondary twins exist in the martensite. Figure 2 shows the morphology of multi-level twinned martensite, such as Figure 2 As shown, there are primary twins inside the needle-shaped martensite, and there are secondary twins inside the primary twins.
[0055] Performance test results: its room temperature tensile yield strength, tensile strength and elongation are 1321MPa, 1402MPa and 6.5% respectively.
[0056] Embodiment 2:
[0057] The only difference from Example 1 is that the power-on time is controlled to be 4s, and the rest is exactly the same.
[0058] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 1281MPa, 1395MPa and 6.6% respectively.
[0059] Embodiment 3:
[0060] The difference from Example 1 is that the power-on time is controlled to be 3.5s, and the rest is exactly the same.
[0061] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 1278MPa, 1389MPa and 6.6% respectively.
[0062] In addition, in Example 2 and Example 3, the titanium alloy matrix is also composed of martensite and twins, wherein the martensite has a length of 0.1-2 μm and an aspect ratio of 1:1-1:12; and primary and secondary twins exist in the martensite.
[0063] Through Examples 1 to 3, it can be seen that: under the same formula, the martensite structure morphology is different when the power-on time is different. Moreover, the inventors have conducted experiments on many materials, and the results show that the increment of 0.5s actually has a great impact on the mechanical properties of the material. The present application can obtain materials with better mechanical properties by controlling the power-on time of the current heat treatment to 3-6s.
[0064] Embodiment 4:
[0065] The difference from Example 1 is that the composition by weight is Al: 7.3%; Mo: 0.8%; Nb: 1%; V: 0.4%; Fe: 0.61%; Cr: 0.45%, and the balance is Ti and unavoidable impurities. The current treatment time is 4s, and the other processes are the same as Example 1.
[0066] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 1232MPa, 1349MPa and 6.4% respectively.
[0067] Embodiment 5:
[0068] The difference from Example 1 is that the composition by weight is Al: 7.4%; Mo: 0.75%; Nb: 1.37%; V: 0.56%; Fe: 0.48%; Cr: 0.57%, and the balance is Ti and unavoidable impurities. The current treatment time is 3.8s, and the other processes are the same as Example 1.
[0069] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 1281MPa, 1376MPa and 6.1% respectively.
[0070] Embodiment 6:
[0071] The difference from Example 1 is that the composition by weight is Al: 6.7%; Mo: 1.5%; Nb: 0.56%; V: 0.52%; Fe: 0.4%; Cr: 0.6%, and the balance is Ti and unavoidable impurities. The current treatment time is 3.3s, and the other processes are the same as Example 1.
[0072] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 1297MPa, 1392MPa and 6.2% respectively.
[0073] Comparative Example 1:
[0074] The difference from Example 1 is that the composition by weight is Al: 6.2%; Mo: 2.02%; Nb: 1.95%; V: 2.6%; Fe: 1.18%; Cr: 0.55%, and the balance is Ti and unavoidable impurities. The current treatment time is 4.5s, and the other processes are the same as Example 1.
[0075] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 356MPa, 1198MPa and 12.7% respectively.
[0076] Comparative Example 2:
[0077] The difference from Example 1 is that the composition by weight is Al: 7.8%; Mo: 4%; Nb: 0.95%; Zr: 3.8%; Fe: 0.58%; Cr: 1.08%, and the balance is Ti and unavoidable impurities. The current treatment time is 4.3s, and the other processes are the same as Example 1.
[0078] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 326MPa, 1214MPa and 12.8% respectively.
[0079] Comparative Example 3:
[0080] The difference from Example 1 is that the composition by weight is Al: 6.2%; Mo: 2%; Nb: 1%; Zr: 3%; Fe: 1.08%; Cr: 1.16%, and the balance is Ti and unavoidable impurities. The current treatment time is 4s, and the other processes are the same as Example 1.
[0081] Performance test results: room temperature tensile yield strength, tensile strength and elongation are 382MPa, 1144MPa and 17.5% respectively.
[0082] From Examples 4 to 6, it can be seen that within the range of the titanium alloy composition system of the present invention, a slight change in composition has little effect on the performance of the material, and the alloy performance is relatively stable. Moreover, after the current heat treatment of the present invention, the strength of the material is at a relatively high level.
[0083] Through Examples 1 to 6 and Comparative Examples 1 to 3, it can be seen that: when the content of β-stabilizing elements is high, many metastable β phases will be produced after current treatment, so that the material will have phase change induced plasticity during the stretching process. Although it shows a high elongation, the yield strength is extremely low. Therefore, the content of β-stabilizing elements must be strictly controlled in the present invention, and Mo≤2%; Nb≤2%; V≤1.5%; Cr≤1.5%; Fe≤1.5%. Further preferably, the content of β-stabilizing elements is controlled to be: Mo≤1.5%; Nb≤1.5%; V≤1%; Cr≤1%; Fe≤1%, so that the room temperature tensile yield strength, tensile strength and elongation of the obtained material are all better.
[0084] The description of the present invention is given for the purpose of illustration and description, and is not intended to be exhaustive or to limit the invention to the disclosed form. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for particular uses.
Claims
1. A high specific strength multi-level twinned martensitic titanium alloy, It is characterized in that The composition system of the titanium alloy is: Ti-Al-Mo-Nb-V-Cr-Fe; the weight percentage of each element is: Al: 6% to 9%; Mo: 0.5% ~ 2%; Nb: 0.5% ~ 2%; V: 0.2% ~ 1.5%; Cr: 0.2% ~ 1.5%; Fe: 0.2% to 1.5%, the balance being Ti and inevitable trace impurities.
2. The high specific strength multi-level twinned martensitic structure titanium alloy according to claim 1, It is characterized in that The titanium alloy consists of a martensite α' phase; The titanium alloy is prepared by combining hot rolling and electric current heat treatment and controlling the power-on time during the electric current heat treatment.
3. The high specific strength multi-level twinned martensitic structure titanium alloy according to claim 2, It is characterized in that The titanium alloy has martensite of different scales and a multi-level twin structure inside.
4. The high specific strength multi-level twinned martensitic structure titanium alloy according to claim 3, It is characterized in that The martensite is 0.1 to 10 μm long, and has an aspect ratio of 1:1 to 1:
20.
5. The high specific strength multi-level twinned martensitic structure titanium alloy according to claim 1, It is characterized in that In the titanium alloy, Al: 6.5% to 8.5%. In the titanium alloy, Mo≤1.5%; Nb≤1.5%; V≤1%; Cr≤1%; Fe≤1%.
6. The high specific strength multi-level twinned martensitic structure titanium alloy according to claim 1, It is characterized in that The titanium alloy has a room temperature tensile yield strength greater than 1200 MPa, a room temperature tensile strength greater than 1300 MPa, and a room temperature elongation greater than 6.0%.
7. A method for preparing a high specific strength multi-level twinned martensitic structure titanium alloy according to any one of claims 1 to 6, It is characterized in that The method combines hot rolling with electric current heat treatment and controls the power-on time during the electric current heat treatment to prepare the product, including the following steps: Step 1), weighing the raw materials of each element according to weight percentage; Step 2), placing the raw materials into a vacuum arc melting furnace, evacuating the furnace, filling with argon as a protective gas, and repeatedly melting for multiple times to obtain an ingot; Step 3), placing the ingot in a vacuum heating furnace for heat preservation, and then annealing by furnace cooling; Step 4), heating and heat-insulating the annealed ingot under an inert gas protection atmosphere, and hot rolling to obtain a titanium alloy plate; Step 5), subjecting the titanium alloy plate to current heat treatment and water quenching to obtain a high specific strength multi-level twin martensitic structure titanium alloy.
8. The method for preparing the high specific strength multi-level twinned martensitic structure titanium alloy according to claim 7, It is characterized in that The step of subjecting the titanium alloy plate to current heat treatment and water quenching to obtain a high specific strength multi-level twin martensitic structure titanium alloy refers to using copper electrodes to clamp the titanium alloy plate, applying a power-on voltage, controlling the power-on time, and water quenching to obtain a high specific strength multi-level twin martensitic structure titanium alloy.
9. The method for preparing the high specific strength multi-level twinned martensitic structure titanium alloy according to claim 8, It is characterized in that When the power-on voltage is 220V, the power-on heating time is controlled to be 3 to 6s.
10. The method for preparing the high specific strength multi-level twinned martensitic structure titanium alloy according to claim 8, It is characterized in that In step 3), the holding temperature is 1000° C. to 1200° C., and the holding time is 4 h to 7 h; In step 4), the heating and insulation temperature is 900°C to 1000°C, and the insulation time is 30min to 60min; during hot rolling, the pressing amount per pass is controlled to be 1mm to 0.5mm; Among them, during hot rolling, when the sample thickness is ≥8mm, the pressing amount per single pass is 1mm; when the sample thickness is 4mm≤<8mm, the pressing amount per single pass is 0.75mm; when the sample thickness is <4mm, the pressing amount per single pass is 0.5mm, until the thickness of the ingot reaches the target thickness.
Citation Information
Cited By
Beta titanium alloy based on d-electronic alloy design theory and preparation method thereof
CN119843104A
